Predicting academic procrastination of students based on academic self-efficacy and emotional regulation difficulties - Hamidreza Farhadi Rad; Shima Bordbar; Jamshid Bahmaei; Marjan Vejdani; Ali Reza Yusefi (Scientific Reports, 2025)
Abstract Academic procrastination is one of the major factors that can be a serious obstacle for students to achieve academic progress and success. This research aimed to investigate and predict academic procrastination based on academic self-efficacy and emotional regulation difficulties of students of one of the medical sciences universities in southern Iran in 2024. This descriptive-analytical cross-sectional study was conducted on 290 students of different fields in the south of Iran between January and April 2024. Data was collected using standard questionnaires of academic procrastination, academic self-efficacy, and difficulty in emotional regulation. Descriptive statistics, t-test, ANOVA, Pearson’s correlation coefficient, and multiple linear regression were employed to examine the data using SPSS 23 software. A significant level of 0.05 was considered. The average score of academic procrastination, academic self-efficacy, and difficulty in emotional regulation of the studied students was 66.21 ± 4.06 (out of 108), 59.58 ± 5.84 (out of 120), and 121.42 ± 6.88 (out of 180), respectively, which indicates a moderate level of academic self-efficacy and academic procrastination and a high level of difficulty in emotional regulation. A statistically significant correlation was observed between students’ academic procrastination and academic self-efficacy (r = -0.648, p < 0.001) and the difficulty in emotional regulation (r = 0.701, p < 0.001). Based on the results of multiple linear regression, components of academic self-efficacy, including effort, talent, and context, as well as components of difficulty in emotion regulation, including difficulty in performing purposeful behavior, lack of emotional awareness, limited access to emotional regulation strategies, non-acceptance of emotional responses, difficulty in impulse control, and lack of emotional clarity, were identified as predictors of academic procrastination (p < 0.05). Considering the students’ academic procrastination and the effect of academic self-efficacy and difficulty in emotional regulation on it, it is suggested that university administrators provide the field of improvement and promotion of students’ academic self-efficacy and emotional regulation through holding related courses and workshops so that in this way procrastination can be reduced.